Structural Health Monitoring: Advanced Sensing, Diagnostics and Prognostics - Bing Li; Yongbo Li; Khandaker Noman (Sensors)
Structural Heath Monitoring (SHM) can be considered one of the most prominent emerging components of modern engineering applications [...]